OPTIMALIZATION OF DIGITAL MARKETING IN AN EFFORT TO PROMOTE SEKAPUK VILLAGE TOURISM VILLAGE UJUNGPANGKAH GRESIK SUBDISTRICT - Mufarokhah, Mufarokhah; Zulyanti, Noer Rafikah (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
Sekapuk village a few years ago was included in the category of poor and underdeveloped villages, high social inequality and is a conflict-prone village. But now, Sekapuk Village has become a billionaire village. This is because of a very bold change to turn the former limestone mine into a tourist attraction named Setigi or Selo Tirto Giri located on Jl. Deandles North Coast of East Java. This study aims to find out and analyze the optimization of digital marketing in the promotion of tourism villages in Sekapuk Village, Ujungpangkah District, Gresik Regency. The method used is descriptive qualitative with research instruments in the form of primary data obtained from observations, interviews from several visitors, and exposure of local officials as well as secondary data from literacy studies and other relevant documentation. The findings in this study are the application of appropriate and relevant promotional strategies, namely the digital marketing method as a form of long-term planning by utilizing existing resources is a strategy to attract potential tourists to visit Sekapuk Tourism Village.